APPLICATION OF CALCULATING ELECTRICITY USAGE UMAH LINEAR TREND STAIRCASE WITH LEAST SQUARE METHOD USING MICROSOFT VISUAL BASIC 6.0 - Fany Firmansyah; Elly Agustina J., Skom, MMSi (Jurnal Sistem Informasi, 2004)
One way to analyze the electricity consumption of households are using thecalculation method in statistical science, namely Trend Linear Least Square Method.With this linear trend can be calculated trend value of electricity consumption foreach household. The formula used is:Where: Y t = Total electricity consumption (in KWH)a = Constantb = coefficientt = t YearsThe value of a (constant) and b (coefficient) was first found by calculating the valueof t I (annual coding), the value of Y i (the use of electricity in KWH), t i2, and t i Y ivalue. After that specify the number of t i, Y i, t i2, and t i Y i. Then determine thevalues of a and b. Then the equation of linear trend can be determined based on thevalue of a and b of this. Finally the values of the trend of electricity consumptionevery month can be obtained by using the linear trend equations.Based on the trend, it is concluded fluctuations in electricity consumption of eachhousehold, whether increased or decreased each month in the period 2001-2003.Information about the fluctuations in electricity consumption of each household isvery beneficial for the PLN. PLN parties can know where households are alreadyefficient and inefficient use of electricity. With so can know which households alsoreflects the principle of saving in electricity consumption.